Effect of post-annealing treatment on the structure and luminescence properties of AIN: Tb3+thin films prepared by radio frequency magnetron sputtering - Tucto Salinas K.Y. (2017)
Terbium-doped aluminum nitride thin films have been deposited by radio frequency magnetron sputtering. The influence of annealing treatments on structural, morphological and luminescence properties of the films is examined with the aim to optimize post-deposition annealing conditions. Temperatures starting from 500 up to 1000°C using two annealing techniques were investigated: rapid thermal processing and quartz tube furnace. X-ray diffraction analysis revealed the formation of aluminum oxide and aluminum oxynitride phases at temperatures higher than 750°C. The oxygen content in the surface layer was measured with energy dispersive X-ray. The terbium emission was obtained after excitation either by photons or electrons. The films treated with rapid thermal processing at 750°C resulted in the highest emission. © 2017 Trans Tech Publications, Switzerland.